Transcultural Adaptation of Environmental Health Questionnaire with Attitude, Knowledge, and Skills Scales for Portuguese Nursing Students - Cristina Álvarez-García; Beatriz Edra; Goreti Marques; Catarina Simões; Mª Dolores López-Franco (Nursing Reports)
Background/Objectives: Climate change adversely affects some of the fundamental determinants of health, and children are the population group most vulnerable to exposure to environmental risk factors. The main objective of this study was to validate in the Portuguese context three scales to assess attitudes, knowledge, and skills on children’s environmental health. Methods: A cross-sectional observational study was developed to translate, adapt, and validate the questionnaire consisting of the following three scales: Attitude Scale (SANS_2), knowledge scale (ChEHK-Q), and skills scale (ChEHS-Q). This was carried out in two phases: the translation and adaptation process and the validation process using classical measure theory and item response theory with undergraduate nursing students. Results: We obtained a valid and reliable questionnaire to measure children’s environmental health competence consisting of an attitude scale (α = 0.84), a knowledge scale (Infit = 0.98, Outfit = 0.97, item reliability = 0.98, and people reliability = 0.75), and a skills scale (Infit = 1.00, Outfit = 0.99, item reliability = 0.82, and people reliability = 0.88). The mean score on the attitude scale was 28.15 (5–35) ± 4.61; 14.92 (0–26) ± 4.51 on the knowledge scale; and 42.51 (24–60) ± 6.41 on the skills scale. Conclusions: We found that most Portuguese undergraduate nursing students have very good pro-environmental attitudes and good knowledge and skills in dealing with children’s environmental health. The questionnaire obtained in this study will be useful for comparative studies with other countries and for evaluating the effectiveness of educational interventions.